Brief notes and history of computing in Mexico during 50 years. Issue 2 (3rd March 2020) - Martínez, Genaro J.; Seck-Tuoh-Mora, Juan C.; Chapa-Vergara, Sergio V.; Lemaitre, Christian
ABSTRACT: The history of computing in Mexico cannot be thought without the name of Prof. Harold V. McIntosh (1929–2015). For almost 50 years, in Mexico, he contributed to the development of computer science with wide international recognition. Approximately in 1964, McIntosh began working in the Physics Department of the Advanced Studies Center (CIEA) of the National Polytechnic Institute (IPN), now called CINVESTAV. In 1965, at the National Center of Calculus (CeNaC), he was a founding member of the Master in Computing, first in Latin America. With the support of Mario Baez Camargo and Enrique Melrose, McIntosh continues his research of Martin-Baltimore Computer Center and University of Florida at IBM 709. GRAPHICAL ABSTRACT: